Oxidative stress in the brain causes hypertension via sympathoexcitation - Kishi, Takuya; Hirooka, Yoshitaka (Frontiers in Physiology, 2012)
Activation of the sympathetic nervous system (SNS) has an important role in the pathogenesis of hypertension, and is determined by the brain. Previous many studies have demonstrated that oxidative stress, mainly produced by angiotensin II type 1 (AT1) receptor and nicotinamide adenine dinucleotide phosphate (NAD (P) H) oxidase, in the autonomic brain regions was involved in the activation of the SNS of hypertension. In this concept, we have investigated the role of oxidative stress in the rostral ventrolateral medulla (RVLM), which is known as the cardiovascular center in the brainstem, in the activation of the SNS, and demonstrated that AT1 receptor and NAD (P) H oxidase-induced oxidative stress in the RVLM causes sympathoexcitation in hypertensive rats. The mechanisms in which brain oxidative stress causes sympathoexcitation have been investigated, such as the interactions with nitric oxide (NO), effects on the signal transduction, or inflammations. Interestingly, the environmental factors of high salt intake and high calorie diet may also increase the oxidative stress in the brain, particularly in the RVLM, thereby activating the central sympathetic outflow and increasing the risk of hypertension. Furthermore, several orally administered AT1 receptor blockers have been found to cause sympathoinhibition via reduction of oxidative stress through the inhibition of central AT1 receptor. In conclusion, we must consider that AT1 receptor and the related oxidative stress production in the brain cause the activation of SNS in hypertension, and that AT1 receptor in the brain could be novel therapeutic target of the treatments for hypertension.